2014
DOI: 10.1111/idj.12091
|View full text |Cite
|
Sign up to set email alerts
|

Dental caries experience and periodontal treatment needs of 10- to 15-year old children with type 1 diabetes mellitus

Abstract: The results suggest that children with type 1 diabetes are at higher risk of developing dental caries and periodontal disease. Greater efforts are required to tackle these problem and prevent complications arising from them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0
13

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 19 publications
3
30
0
13
Order By: Relevance
“…The study of Miko et al (25) showed no statistical difference in that regard. Arheiam and Omar reported that the mean number of decayed and missing teeth was higher in diabetic children (26).…”
Section: Discussionmentioning
confidence: 96%
“…The study of Miko et al (25) showed no statistical difference in that regard. Arheiam and Omar reported that the mean number of decayed and missing teeth was higher in diabetic children (26).…”
Section: Discussionmentioning
confidence: 96%
“…Odnotowano więk-szą częstość występowania periodontopatii u pacjentów z późno rozpoznaną lub długo trwającą cukrzycą, nieleczonych czy leczonych nieprawidłowo [26]. Według najnowszych badań nie można jednak uznać cukrzycy za czynnik wywołujący choroby przyzębia, lecz jedynie za modyfikujący i zwiększający ryzyko działania miejscowych czynników zapalnych [27][28][29].…”
Section: Tabela 2 Uzębienie Stałe -Intensywność Próchnicy I Efektywnunclassified
“…The increase in salivary glucose concentration may also influence the development of dental caries (2,19,20). In some cases T1DM may contribute to the severity and intensity of tooth decay, and the resulting caries may interfere with the health of a child with T1DM (21). The caries' progression may increase the risk of infection and imbalance in the glycemic control of diabetes.…”
Section: Introductionmentioning
confidence: 99%